Synthesis of LSMO at low temperature by novel hydroxide precursor technique - Gupta, U. N.; Muthurajan, H.; Kumar, H. H.; Rao, N. Koteswara; Gokhale, Suresh P.; Ravi, V. (Materials Letters, 2008)
A novel technique of mixing individual hydroxide is employed to prepare La0.65Sr0.35MnO3 (LSMO) at low temperature. Freshly prepared lanthanum and manganese hydroxides are mixed thoroughly with strontium hydroxide in stoichiometric ratio and heated at different temperatures ranging from 100 to 500 degrees C for 6 h. At 500 degrees C, formation of La0.65Sr0.35MnO3 was confirmed by the X-ray diffraction studies (XRD). This is the lowest temperature so far reported in the literature. The particle size and morphology were investigated by scanning electron microscopy (SEM). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; La0.65Sr0.35MnO3; Oxides; Precipitation; X-ray diffraction